The Influence of Work Environment and Self Esteem on Employee Performance at Directorate Prisoners and Evidence Bengkulu Police - Muhammad Hafiz Handika; Ahmad Soleh; Rinto Noviantoro (Jurnal Fokus Manajemen, 2021)
The purpose of this study is to determine the influence of work environment and self esteem on employee performance at Directorate Prisoners and Evidence Bengkulu Police. This research is a descriptive quantitative study with data collection methods through distributing questionnaires. The sample in this study were all employees of the Directorate Prisoners and Evidence Bengkulu Police totaling 55 employees using the sampling method is total sampling or census. The data analysis method used includes validity test, reliability test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that work environment and self esteem partially have a positive and significant effect on employee performance at Directorate Prisoners and Evidence Bengkulu Police. And well as simultaneously work environment and self esteem have a significant effect on employee performance at Directorate Prisoners and Evidence Bengkulu Police.